2016
DOI: 10.1136/bcr-2015-212547
|View full text |Cite
|
Sign up to set email alerts
|

A cautionary approach to adult female groin swelling: hydrocoele of the canal of Nuck with a review of the literature

Abstract: Hydrocoele of the canal of Nuck in an adult female is a rare entity and analogous to hydrocoele in males. Its usual presentation is in children, and its occurrence in adults is very uncommon, more so of the hour-glass variety. We report a case of a 38-year-old woman presenting with a right inguinal swelling of 3-month duration. On physical examination, the swelling was non-tender, cystic and irreducible. There was no cough impulse. Ultrasonography and contrast-enhanced CT revealed a cystic swelling with clear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 12 publications
1
35
1
Order By: Relevance
“…2,4,10,14 Among the cases reported as cysts of Nuck’s canal, most patients were also middle-aged. 6,8,1114 These data together with ours suggest that MCURLs occur mostly in middle-aged women. In our series, 64.7% (11/17) of the patients had an MCURL on the right side, which is in line with the findings of other studies showing right-side dominance in MCURL occurrence.…”
Section: Discussionsupporting
confidence: 75%
“…2,4,10,14 Among the cases reported as cysts of Nuck’s canal, most patients were also middle-aged. 6,8,1114 These data together with ours suggest that MCURLs occur mostly in middle-aged women. In our series, 64.7% (11/17) of the patients had an MCURL on the right side, which is in line with the findings of other studies showing right-side dominance in MCURL occurrence.…”
Section: Discussionsupporting
confidence: 75%
“…Some authors have reported that the prevalence of inguinal swelling in pediatric patients is <1% [7]. However, few studies on the prevalence of HCN in adult patients have been reported [8,9]. According to our data, among 174 adult patients with inguinal swelling, 56 (32.2%) had HCN, which is a much higher prevalence than that reported in the current literature [6,8].…”
Section: Discussioncontrasting
confidence: 55%
“…Cardinal ultrasonographic signs include a homogenous, cystic, superficial mass which does not change with Valsalva manoeuvre. 15 17 18 …”
Section: Discussionmentioning
confidence: 99%